The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1016/j.bjane.2021.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Use of simulation to teach in the operating room – Don't let the COVID-19 pandemic interrupt education:an observational clinical trial

Abstract: Background Simulation-based education has become the most important part of resident training in anesthesiology, especially during the pandemic. It allows learning the skills and the management of different situations without putting residents in risk of contamination, considering COVID-19 is highly contagious. The hypothesis was that simulation is still associated with improvement of knowledge acquisitions despite the context of the COVID-19 pandemic. Methods Residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Additionally, studies by Zarifsanaiey et al ( 2016 ), Offiah et al ( 2019 ) and Korayem et al ( 2020 ), as well as those incorporated in McGaghie et al’s ( 2011 ) review, have shown that when face-to-face simulations are supplemented or integrated with other teaching or clinical training methods, pharmacy, medical and nursing students’ knowledge and clinical task skills and retention thereof is further enhanced. Furthermore, to allow for the continuation of clinical training of HCPs in the COVID-19 era, some programmes, like anaesthesiology programmes, implemented face-to-face simulations as a mode of clinical training (Büyük et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies by Zarifsanaiey et al ( 2016 ), Offiah et al ( 2019 ) and Korayem et al ( 2020 ), as well as those incorporated in McGaghie et al’s ( 2011 ) review, have shown that when face-to-face simulations are supplemented or integrated with other teaching or clinical training methods, pharmacy, medical and nursing students’ knowledge and clinical task skills and retention thereof is further enhanced. Furthermore, to allow for the continuation of clinical training of HCPs in the COVID-19 era, some programmes, like anaesthesiology programmes, implemented face-to-face simulations as a mode of clinical training (Büyük et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…One way to enhance medical and nursing students' skill retention is for them to repeat the simulation activities (Eide et al, 2020;Offiah et al, 2019). Additionally, studies by Zarifsanaiey et al (2016), Offiah et al (2019) and Korayem et al (2020) (Büyük et al, 2021).…”
Section: Face-to-face Simulation As a Mode Of Clinical Trainingmentioning
confidence: 99%
“…This approach mitigated the risk of patient exposure for trainees and provided a secure learning environment. [ 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…For all the reasons above, in this issue of the Brazilian Journal of Anesthesiology , we invite readers to access several interesting studies providing new insights into the role of the anesthesiologist in the COVID-19 pandemic. 14 , 15 , 16 , 17 , 18 , 19 , 20 These studies have addressed a myriad of COVID-19-related topics, including the risk for environmental exposure to the SARS-CoV-2, potential protective measures to reduce contamination during airway management, mental health of healthcare providers and education concerns during the pandemic, a new technique for percutaneous tracheostomy in COVID-19 patients, and potential benefits of early awake prone positioning in patients displaying COVID-19-related ARDS.…”
mentioning
confidence: 99%